Angiotensin–neprilysin inhibition and renal outcomes across the spectrum of ejection fraction in heart failure. (18th January 2022) - Mc Causland, Finnian R.; Lefkowitz, Martin P.; Claggett, Brian; Packer, Milton; Senni, Michele; Gori, Mauro; Jhund, Pardeep S.; McGrath, Martina M.; Rouleau, Jean L.; Shi, Victor; Swedberg, Karl; Vaduganathan, Muthiah; et al.
Abstract: Aims: Patients with heart failure are at higher risk of progression to end‐stage renal disease (ESRD), regardless of ejection fraction (EF). We assessed the renal effects of angiotensin–neprilysin inhibition in a pooled analysis of 13 195 patients with heart failure with reduced and preserved EF. Methods and results: We combined data from PARADIGM‐HF (EF ≤40%; n = 8399) and PARAGON‐HF (EF ≥45%; n = 4796) in a pre‐specified pooled analysis. We assessed the effect of treatment (sacubitril/valsartan vs. enalapril or valsartan) on a composite of either ≥50% reduction in estimated glomerular filtration rate (eGFR), ESRD, or death from renal causes, in addition to changes in eGFR slope. We assessed whether baseline renal function or EF modified the effect of therapy on renal outcomes. At randomization, eGFR was 68 ± 20 ml/min/1.73 m 2 in PARADIGM‐HF and 63 ± 19 ml/min/1.73 m 2 in PARAGON‐HF. The composite renal outcome occurred in 70 of 6594 patients (1.1%) in the sacubitril/valsartan group and in 123 of 6601 patients (1.9%) in the valsartan or enalapril group (hazard ratio 0.56, 95% confidence interval [CI] 0.42–0.75; p < 0.001). The mean eGFR change was −1.8 (95% CI −1.9 to −1.7) ml/min/1.73 m 2 /year for the sacubitril/valsartan group, compared with −2.4 (95% CI −2.5 to −2.2) ml/min/1.73 m 2 /year for the valsartan or enalapril group. The treatment effect on the composite renal endpoint was not modified by categories of baseline eGFR ( p ‐interaction = 0.64), but was most pronounced in those with baseline EF between 30% and 60% ( p ‐interaction = 0.001). Conclusions: In patients with heart failure, sacubitril/valsartan reduced the risk of serious adverse renal outcomes and slowed decline in eGFR, compared with valsartan or enalapril, independent of baseline renal function.